141 DIFFERENT KINETICS OF NT-PROBNP AND S-ST2 HIGHLIGHT DIFFERENT THERAPEUTIC THERAPEUTIC PATHWAYS OF SACUBITRIL/VALSARTAN. (15th December 2022) - Mapelli, Massimo; Mattavelli, Irene; Salvioni, Elisabetta; Bonomi, Alice; Palermo, Pietro; Banfi, Cristina; Paolillo, Stefania; Biondi, Maria Luisa; Agostoni, Piergiuseppe
Abstract: Background: N-terminal pro-B-type natriuretic peptide (NT-proBNP) and soluble interleukin 1 receptor-like 1 ST2 (sST2) are biomarkers used to grade heart failure with reduced ejection fraction (HFrEF) severity. The first is associated with the patient's hemodynamic status, while the second is indicative of the inflammatory component and of myocardial fibrosis and both are potential targets of HFrEF treatment. Aim of the study: The aim of this study was to assess the kinetics of these biomarkers after treatment with sacubitril/valsartan in HFrEF. Methods: We analyzed blood samples of HFrEF patients at baseline (before sacubitril/valsartan treatment), after 1, 2, 3 months (respectively after a month taking the 24/26–49/51–97/103mg doses), and 6 months after the maximum tolerated dose was reached (end-study). Results: We obtained samples from 34 HFrEF patients (age 65.9±9.0, 74% males). NT-proBNP and sST2 values progressively and significantly reduced up to 21%±33 and 9%±16, respectively, with a greater reduction for NT-proBNP (p<0.05). Specifically, NT-proBNP reduced from 1286 [609-3205] to 877 [437-1866] pg/mL and sST2 from 29.3 [19.5-34.1] to 20.4 [15.6-28.9] ng/mL, p<0.05 in both cases). The reduction of the two biomarkers over time occurred with statistically significant different kinetics: deferred for sST2 and faster for NT-proBNP. No significant changes in renal function and potassium levels were recorded. Conclusions: These findings suggest that, in HF patients, sacubitril/valsartan effects on the cardiovascular system share a double pathway: a first, hemodynamic, faster pathway and a second, non-hemodynamic, delayed pathway. Both likely contribute to the sacubitril/valsartan benefits in HFrEF.